2013
DOI: 10.1093/rheumatology/ket134
|View full text |Cite
|
Sign up to set email alerts
|

The role of high mobility group box chromosomal protein 1 in rheumatoid arthritis

Abstract: High mobility group box chromosomal protein 1 (HMGB1) is a ubiquitous highly conserved single polypeptide in all mammal eukaryotic cells. HMGB1 exists mainly within the nucleus and acts as a DNA chaperone. When passively released from necrotic cells or actively secreted into the extracellular milieu in response to appropriate signal stimulation, HMGB1 binds to related cell signal transduction receptors, such as RAGE, TLR2, TLR4 and TLR9, and becomes a proinflammatory cytokine that participates in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 93 publications
3
36
0
Order By: Relevance
“…Concentrations of LPS used for HMGB1 stimulation in this study were not cytotoxic to OLC-1 cells (data not shown). Our results on changes in HMGB1 in OLC-1 cells are consistent with those of previous studies in which HMGB1 is actively secreted from LPS-activated immune and nonimmune cells involved in chronic inflammatory diseases [5052]. Furthermore, HMGB1 was solely localized in the nucleus of odontoblasts in healthy tissues, while a significant proportion of HMGB1 translocated to the cytoplasm in pulpitis tissue, which correlates with an increase in extracellular HMGB1 in LPS stimulated OLC-1 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Concentrations of LPS used for HMGB1 stimulation in this study were not cytotoxic to OLC-1 cells (data not shown). Our results on changes in HMGB1 in OLC-1 cells are consistent with those of previous studies in which HMGB1 is actively secreted from LPS-activated immune and nonimmune cells involved in chronic inflammatory diseases [5052]. Furthermore, HMGB1 was solely localized in the nucleus of odontoblasts in healthy tissues, while a significant proportion of HMGB1 translocated to the cytoplasm in pulpitis tissue, which correlates with an increase in extracellular HMGB1 in LPS stimulated OLC-1 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the antibody treatments reduced the production of key pro‐inflammatory cytokines, IL‐12 and TNF‐ α , which play a pathogenic role in many pro‐inflammatory and autoimmune diseases . This is consistent with previous reports that TLR2 and TLR4 signals are generally pro‐inflammatory in other inflammatory arthritis models and suggests that the anti‐inflammatory effect observed here may extend beyond CIA to other inflammatory disorders . While the detailed mechanisms are still unknown, the neutralizing antibodies could block the TLRs‐mediated effects by directly antagonizing the ligand/TLRs interaction in the arthritic context.…”
Section: Discussionsupporting
confidence: 90%
“…While the detailed mechanisms are still unknown, the neutralizing antibodies could block the TLRs‐mediated effects by directly antagonizing the ligand/TLRs interaction in the arthritic context. The possible TLR2 ligands may include the endogenous gp96 and serum amyloid A and extraneous mycobacteria components present in the complete adjuvant . Possible TLR4 ligands may be the endogenous fibrinogen, hyaluronic acid and HMGB‐1 and exogenous LPS, which are present in vivo and proven important for the induction of CIA …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated that acetylation and phosphorylation of HMGB‐1 regulated HMGB‐1 transporting to the cytoplasm . In monocytes, a non‐classical vesicle compartment‐mediated pathway and exocytosis of secretory lysosomes had regulated the HMGB‐1 transporting to extracellular matrix .…”
Section: Discussionmentioning
confidence: 99%